A comparison of land use change accounting methods: seeking common grounds for key modeling choices in biofuel assessments. (10th March 2018) - Saez de Bikuña, Koldo; Hamelin, Lorie; Hauschild, Michael Zwicky; Pilegaard, Kim; Ibrom, Andreas
Abstract: Five currently used methods to account for the global warming (GW) impact of the induced land-use change (LUC) greenhouse gas (GHG) emissions have been applied to four biofuel case studies. Two of the investigated methods attempt to avoid the need of considering a definite occupation –thus amortization– period by considering ongoing LUC trends as a dynamic baseline. This leads to the accounting of a small fraction (0.8%) of the related emissions from the assessed LUC, thus their validity is disputed. The comparison of methods and contrasting case studies illustrated the need of clearly distinguishing between the different time horizons involved in life cycle assessments (LCA) of land-demanding products like biofuels. Absent in ISO standards, and giving rise to several confusions, definitions for the following time horizons have been proposed: technological scope, inventory model, impact characterization, amortization/occupation, plantation lifetime and harvesting frequency. It is suggested that the anticipated technical lifetime of biorefineries using energy crops as feedstock stands as the best proxy for the cut-off criterion of land's occupation period and the inventory modeling period. Top-down LUC models are suggested as a gross reference benchmark to evaluate LUC results from bottom-up models, since the former represent average GHG emissions from deforestation statistics at different spatial resolutions. Reporting LUC emissions per area and implementing a corporate accounting system that ascribes deforestation emissions to responsible companies could avoid the critical uncertainty related to yield estimations. Highlights: The technical lifetime of a biorefinery is suggested as the best possible estimate for land's long-term occupation. The validity of current dynamic baseline methods to account for GHG emissions from deforestation LUC is disputed. Top-down LUC models give average GHG emissions at different spatial scales which can be used to assess the validity of bottom-up model results.